Apakah Brand Image Dan Brand Attitude Berpengaruh Terhadap Brand Equity ? - Nur Sania, Utari; Sabran , Sabran; Anggar Sari , Nilam (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The purpose of this study was to determine the effect of brand image and brand attitude either simultaneously or partially on brand equity. Besides that, to find out the variables that have the most dominant influence on brand equity at Pondok Three All restaurants in Tenggarong. The analytical tool used is multiple regression with the number of samples in this study as many as 74 people. The results of the study show that: First, the calculation results from the F test or simultaneously indicate that brand image and brand attitude have a significant influence on brand equity, so that the proposed hypothesis is accepted. Second, the results of the t test or partially show that brand image and brand attitude have a positive and significant effect on brand equity at Pondok Three All Restaurant in Tenggarong, so that the proposed hypothesis is accepted. Judging from the two independent variables, the variable that has the most dominant influence is brand attitude (X2), thus the fourth hypothesis proposed is accepted because it is proven true.